2015
DOI: 10.1016/j.apjtm.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Leptospira isolated from rats catched in Yogyakarta Indonesia

Abstract: It can be considered that rats are the most important vector and reservoir of Leptospira.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Study by Sumanta (2015), mentioned of 99 rat kidneys examined for Leptospira DNA, 25 came out positive using qPCR and 6 was positively confirmed for pathogenic Leptospira using standard PCR. Pathogenic Leptospira examination using LipL 32 gene target were already performed in water sample from nine villages in Demak district and resulted 46.7% positively containing pathogenic Leptospira DNA (Widiastuti, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…Study by Sumanta (2015), mentioned of 99 rat kidneys examined for Leptospira DNA, 25 came out positive using qPCR and 6 was positively confirmed for pathogenic Leptospira using standard PCR. Pathogenic Leptospira examination using LipL 32 gene target were already performed in water sample from nine villages in Demak district and resulted 46.7% positively containing pathogenic Leptospira DNA (Widiastuti, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…Rodents were first discovered as reservoirs and natural hosts capable of sustaining the presence of Leptospira without exhibiting symptoms. Several research findings revealed that several types of rodents tested positive for Leptospira bacteria in various areas [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Rodents have been reported as the primary reservoirs of pathogenic leptospires, reason why there are numerous investigations worldwide with variable infection rates (Agudelo-Flórez et al 2009, Sumanta et al 2015. This characteristic is due to the ability of Leptospira spp.…”
Section: Inroductionmentioning
confidence: 99%